Custom-Made Foot Orthoses as Non-Specific Chronic Low Back Pain and Pronated Foot Treatment - Castro-Méndez, Aurora; Palomo-Toucedo, Inmaculada Concepción; Pabón-Carrasco, Manuel; Ramos-Ortega, Javier; Díaz-Mancha, Juan Antonio; Fernández-Seguín, Lourdes María (International journal of environmental research and public health, 2021)
Excessive foot pronation has been reported as being related to chronic low back pain symptoms and risk factors in sports-specific pathologies. Compensating custom-made foot orthotics treatment has not been entirely explored as an effective therapy for chronic low back pain (CLBP). This study aims to observe the effects of custom-made foot orthoses, in subjects with foot pronation suffering from CLBP. A total of 101 patients with nonspecific CLBP and a pronated foot posture index (FPI) were studied. They were randomized in two groups: an experimental one (n = 53) used custom-made foot orthotics, and the control group (n = 48) were treated with non-biomechanical effect orthoses. The CLBP was measured using the Oswestry Disability Index (ODI) Questionnaire and a visual analogue scale (VAS), both for lower back pain. The symptoms were evaluated twice, at first when the subject was included in the study, and later, after 4 weeks of treatment. The analysis of outcomes showed a significant decrease in CLBP in the custom-made foot orthoses participants group (p < 0.001 ODI; p < 0.001 VAS). These findings suggest that controlling excessive foot pronation by using custom-made foot orthoses may significantly contribute to improving CLBP.